2018
DOI: 10.1053/j.gastro.2017.10.043
|View full text |Cite
|
Sign up to set email alerts
|

MIR21 Drives Resistance to Heat Shock Protein 90 Inhibition in Cholangiocarcinoma

Abstract: Background & AimsCholangiocarcinomas (CCA) are resistant to chemotherapy, so new therapeutic agents are needed. We performed a screen to identify small-molecule compounds that are active against CCAs. Levels of microRNA 21 (MIR21 or miRNA21) are increased in CCAs. We investigated whether miRNA21 mediates resistance of CCA cells and organoids to HSP90 inhibitors.MethodsWe performed a high-throughput screen of 484 small-molecule compounds to identify those that reduced viability of 6 human CCA cell lines. We tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 63 publications
4
98
0
Order By: Relevance
“…Encouragingly, a recent report has hinted that ICC cells are addicted to HSP90 regardless of their mutational landscape. (29) We therefore suggest that the anticancer effects of HSP90 inhibitors in FF-expressing ICCs might integrate suppression of the main oncogenic driver (i.e., FFs themselves), with inhibition of other client/s playing a necessary role in maintaining the ICC transformed phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…Encouragingly, a recent report has hinted that ICC cells are addicted to HSP90 regardless of their mutational landscape. (29) We therefore suggest that the anticancer effects of HSP90 inhibitors in FF-expressing ICCs might integrate suppression of the main oncogenic driver (i.e., FFs themselves), with inhibition of other client/s playing a necessary role in maintaining the ICC transformed phenotype.…”
Section: Discussionmentioning
confidence: 91%
“…The levels of miR-433 and miR-22 were down-regulated in CCA, and restoration of these miRNAs contributed to ciliary restoration and decreased the malignant phenotype of cancer cells by targeting histone deacetylase 6 [9]. Furthermore, miR-21 was highly expressed in CCA and appeared to mediate resistance of CCA cells to HSP90 inhibitors by reducing levels of DNAJB5 [10].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Recently, increasing researches have revealed that miRNAs were powerful regulators in the tumorigenesis of CCA [9,10]. The levels of miR-433 and miR-22 were down-regulated in CCA, and restoration of these miRNAs contributed to ciliary restoration and decreased the malignant phenotype of cancer cells by targeting histone deacetylase 6 [9].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Lampis et al . (11) demonstrated that miR-21 targets genes that act as target proteins for HSP90 in human CCA cell lines and inhibition of this miRNA helps reduce CCA progression. Saha et al .…”
Section: Epigenetics and Post-transcriptional Modificationmentioning
confidence: 99%